Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1148/radiol.2233010680
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis: Assessment of Severity with Clinical and CT Evaluation

Abstract: Treatment of patients with acute pancreatitis is based on the initial assessment of disease severity. Severe pancreatitis occurs in 20%-30% of all patients with acute pancreatitis and is characterized by a protracted clinical course, multiorgan failure, and pancreatic necrosis. Early staging is based on the presence and degree of systemic failure (cardiovascular, pulmonary, renal) and on the presence and extent of pancreatic necrosis. Individual laboratory indexes (markers of pancreatic injury, markers of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
421
2
41

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(511 citation statements)
references
References 64 publications
21
421
2
41
Order By: Relevance
“…Our study confirmed the importance of pancreatic necrosis in determining disease severity as previously reported [4,[13][14][15][16][17][18]. Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study confirmed the importance of pancreatic necrosis in determining disease severity as previously reported [4,[13][14][15][16][17][18]. Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed no mortality was reported in low CTSI scores whereas a 17% mortality was associated with high scores. However, the usefulness appears questionable for clinical management of patients with an intermediate score (3)(4)(5)(6) that is associated with a 6% mortality rate. Indeed in our patient population, even with an optimized cutoff point, the sensitivity does not exceed 80% with a specificity of 55% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of CT scan was recorded and Balthazar CT severity score calculated for the purposes of the study [19]. For tertiary transfer patients, the information relating to CT refer to scans undertaken in this centre.…”
Section: Use Of Computed Tomography (Ct)mentioning
confidence: 99%
“…The CRP test is widely available in laboratories, and various researchers have suggesting using CRP as a prognostic marker for severe AP (9). However, a primary problem is the lack of specificity to predict severe AP at a level not greater than 80% (2,10,11).…”
Section: Introductionmentioning
confidence: 99%